STEM-11. CD146/MCAM REGULATES MESENCHYMAL PROPERTIES, STEMNESS, RADIO-RESISTANCE AND YAP ACTIVITY IN GLIOBLASTOMA. (11th November 2019) - Liang, Yuan-Ke; Voshart, Daniëlle; den Dunnen, Wilfred; Barazzuol, Lara; Kruyt, Frank
Abstract: Glioblastoma (GBM), a highly malignant and lethal brain tumor, is characterized by diffuse invasion into the brain and chemoradiotherapy resistance resulting in recurrences and poor prognosis. In this study we examined if the cell adhesion molecule CD146/ MCAM is contributing to the malignant properties of GBM, as it is known to have multiple protumorigenic functions in other tumor types. TCGA GBM database analyses revealed enhanced levels of CD146 in GBM compared to normal brain. A panel of patient-derived GBM spheroids, enriched for GBM stem cells (GSC), displayed variable and modest expression of CD146 that was strongly enhanced by cell adherence mediated by serum differentiation or ECM-coating. TGF-β-induced mesenchymal transition in U87 cells was accompanied by induction of CD146 expression, whereas ectopic overexpression of CD146/GFP in GG16 spheroids increased mesenchymal marker expression and cell invasion. Conversely, CRISPR/Cas9-generated CD146 knockouts in GSC23 spheroids led to reduced mesenchymal marker expression and invasion. These results were confirmed by applying embryonic stem cell-derived brain organoids as models to study invasion. Hence, GBM spheroid - brain organoid fusions demonstrated a stimulatory function of CD146 on invasion. Moreover, stem cell marker expression and clonogenic assays showed that CD146 increases the stem cell potential of GBM cells. The CD146 ectopic overexpression and knockout models also demonstrated involvement of CD146 in resistance to radiation that could be mechanistically linked with CD146-dependent suppression of p53 accumulation and activation of NF-kB. Interestingly, exploration of additional mechanisms potentially involved in CD146 functioning, led to the discovery that the oncogenic protein Yes-associated protein (YAP) is also regulated by CD146. Together, our findings demonstrate the importance of CD146 in controlling tumor aggressiveness and radioresistance in GBM cells.